مبدأ الرضا في عقود التجارة الدولية - هدى سوداني; سامية ذوايبية (My University, 2025)
Abstract International Trade is often the engine of growth, as they contribute significantly to the increase in economic activity of the countries of the world and this is what pushes companies to organize international contractual relations with an element of foreignness and is the basis of the will of the parties based on the principle of freedom of contract will power to determine the law applicable to international contracts, they will hit some legal problems of their application is necessary on the rules application of public policy and applicable by the judge and also on the functional transformation of the will of the parties as a base and the integration of will in international contracts as a condition of the contract for Algerian law has placed allocation of legislature rigid controls regarding contractual obligations in the text of Article 18 of the Algerian ............................. تعتبر التجارة الدولیة في كثیر من الأحیان محرك النمو، كونها تساهم بشكل كبیر في زیادة النشاط الاقتصادي لدول العالم ، و هذا ما یدفع بالتعامل التجاري على الصعید الدولي أن یرتب نشوء علاقات تعاقدیة ذات عنصر أجنبي و یكون أساس هذه العلاقة ارادة الاطراف استنادا إلى لمبدأ سلطان الإ رادة و حریة المتعاقدین في تحدید القانون الواجب التطبیق على العقود الدولیة إلا أن هذه الإرادة قد تصطدم ببعض الإشكالات القانونیة لتطبیقها ألا و هي القواعد ذات التطبیق الضروري المتعلقة بالنظام العام للدولة و الواجبة التطبیق من قبل القاضي و كذالك التحول الوظیفي لإرادة الأطراف كضابط إسناد و اندماج الإرادة في العقود الدولیة كشرط في العقد ، و بالنسبة التشریع الجزائري فقد وضع المشرع ضوابط إسناد جامدة في خصوص الالتزامات التعاقدیة في نص المادة 18 من التقنین المدني الجزائري و قید حریة الأطراف في مجال إبرام العقود الدولیة . ...................... Le Commerce international est souvent le moteur de la croissance, car ils contribuent considérablement à l'augmentation de l'activité économique des pays du monde et c'est ce qui pousse les entreprises au niveau international pour organiser des relations contractuelles avec un élément d'extranéité et est la base de la volonté des parties fondé sur le principe de la liberté de volonté de puissance du contrat pour déterminer la loi applicable aux contrats internationaux, ceux-ci seront ont frappé certains juridique des problèmes de leur application est nécessaire sur les règles d'application de l'ordre public, et applicable par le juge et aussi sur la transformation fonctionnelle de la volonté des parties comme base et l'intégration de volonté dans les contrats internationaux comme une condition du contrat, pour la législation algérienne a mis l'affectation de contrôles législature de rigides en ce qui concerne les obligations contractuelles dans le texte de l'article 18 du code civil algérien eten vertu de la liberté des parties aux contrats internationaux.
Keywords: :Keywords International trade; internationality; right to the will; the explicit intention; implied commitment; integration of wills; the functional .transformation of the will; الكلمات المفتاحیة : -1 التجارة الدولیة - معیار الدولیة -قانون الإ رادة – الإرادة الصریحة - الإرادة الضمنیة - اندماج الإرادة - التحول الوظیفي لقانون الإرادة.; Mots clés : Commerce international; l’internationalité; droit de la volonté; la volonté explicite; la volonté implicite; intégration des volontés; la transformation fonctionnelle de la volonté.